2021
DOI: 10.1002/adom.202100755
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl‐Rich d‐Sorbitol to Address Transport Layer/Perovskite Interfacial Issues toward Highly Efficient and Stable 2D/3D Tin‐Based Perovskite Solar Cells

Abstract: Organic-inorganic hybrid perovskite solar cells (PSCs) based on tin (Sn) have attracted widespread attention due to their excellent optical and electrical properties similar to lead (Pb)-based analog and more importantly, these Sn-based perovskites owning intrinsic low-toxicity features have broader commercial application prospect. [1][2][3] And compared to Pb-based analog, Sn-based perovskite features a smaller optical bandgap and a more rapid charge-carrier mobility, both of which enable it to absorb more in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Sn 2+ is easily oxidized to Sn 4+ , accompanied by the phase instability of CsSnI 3 perovskite, leading to rapid degradation of its performance. [32][33][34] It is an urgent need to find a new approach to simultaneously improve the stability and PCE of CsSnI 3 PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Sn 2+ is easily oxidized to Sn 4+ , accompanied by the phase instability of CsSnI 3 perovskite, leading to rapid degradation of its performance. [32][33][34] It is an urgent need to find a new approach to simultaneously improve the stability and PCE of CsSnI 3 PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the lm based on toluenewashed SnI 2 had the lowest amount of Sn 4+ impurities, which can trap photon-generated carriers and should be avoided. 45 The above results prove that the use of high-purity SnI 2 could improve the lm morphology, optical properties, and crystalline quality, and decrease the content of detrimental Sn 4+ impurities, all of which are highly related to solar cell performance.…”
Section: Resultsmentioning
confidence: 64%
“…It is observed that both the control and EABr-containing perovskite samples show continuous films. The control perovskite film exhibits noncompact morphology with a certain number of surface fluctuations, which may lead to a multitude of charge trap sites as recombination centers, impeding effective carrier transport and extraction and resulting in severe leakage currents, thus reducing device performance. , Moreover, these defects may act as oxidation sites for Sn 2+ which would produce more tin vacancies, leading to more severe nonradiative recombination Figure S2 present SEM images of 2% and 8% EABr-containing perovskite films.…”
Section: Resultsmentioning
confidence: 99%